(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The principles on which the first generation of Communicative Language Teaching materials are still relevant to language teaching today, so in this article we will briefly review the main activity types that were one of the outcomes of Communicative Language Teaching. One of the goals of Communicative Language Teaching is to develop fluency in language use